2011
DOI: 10.1111/j.1365-2850.2011.01723.x
|View full text |Cite
|
Sign up to set email alerts
|

Parenting styles and eating disorders

Abstract: The aim of the study was to analyse the parental bonding profiles in patients with eating disorders (ED), as well as the relationship among the different styles of parenting and some psychological and psychopathological variables. In addition, the association between the perceived parental bonding and different coping strategies was analysed. Perception of parenting styles was analysed in a sample of 70 ED patients. The Parental Bonding Instrument, Self-Esteem Scale of Rosenberg, Coping Strategies Inventory, S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
19
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(27 citation statements)
references
References 40 publications
(73 reference statements)
4
19
0
3
Order By: Relevance
“…Several studies have documented an association between a bonding behavior pattern characterized by low care and high protectiveness and eating symptomatology [130,131]. In line with previous empirical research [36], the model tested showed that poor parental care does not have a direct effect on ED risk, but it has a significant indirect effect through low self-esteem.…”
Section: Structural Equation Modeling Of Possible Risk Factors For Easupporting
confidence: 67%
“…Several studies have documented an association between a bonding behavior pattern characterized by low care and high protectiveness and eating symptomatology [130,131]. In line with previous empirical research [36], the model tested showed that poor parental care does not have a direct effect on ED risk, but it has a significant indirect effect through low self-esteem.…”
Section: Structural Equation Modeling Of Possible Risk Factors For Easupporting
confidence: 67%
“…While there is other research supporting the link between clinically diagnosed eating disorders and low parental warmth (e.g., Lobera, Rios, & Casals, 2011;Swanson et al, 2010), there is also a large amount of research that specifically examines the connections between parental warmth (or closely related measures) and poor body image and disordered eating. For instance, increases in disordered eating in over 5,000 adolescent girls was associated with low levels of parental caring (Neumark-Sztainer, Story, Hannan, Beuhring, & Resnick, 2000), which is often referred to as warmth.…”
Section: Parental Messages Regarding Weightmentioning
confidence: 99%
“…Though the potential causes of these results are complex, they are undoubtedly of both scientific and practical significance for several reasons. Previously, the effect of parental warmth had only been studied with those who had developed disordered eating symptoms or clinically diagnosable eating disorders (e.g., Deas et al, 2011;Lobera et al, 2011;Mangweth et al, 2005;Neumark et al, 2000;Swanson et al, 2010), with the exception of a study by Haycraft and Blissett (2010), which did note that the relationship between authoritarian parents and the development of drive for thinness in girls was particularly strong. The current study establishes that there is indeed a relationship between warmth and drive for thinness, a known precursor to the development of disordered eating.…”
Section: Parental Warmth and Girls' Drive For Thinnessmentioning
confidence: 99%
See 1 more Smart Citation
“…A literatura aponta que entre os fatores de risco para o surgimento de AN na infância e adolescência estão os déficits de habilidades socioemocionais dos pais e estilos parentais inadequados (Canetti, Kanyas, Lerer, Latzer, & Bachar, 2008;Cella, Iannaccone & Cotrufo, 2013;Enten & Golan, 2009;Horesh, et al, 2015;Jauregui-Lobera, Bolanos-Rios, & Garrido-Casals, 2011;Tetley, Moghaddam, Dawson, & Rennoldson, 2014;Robinson, Strahan, Girz, Wilson, & Boachie, 2013).…”
Section: Justificativaunclassified